2016
DOI: 10.5152/jtgga.2016.15235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index and age on in vitro fertilization in polycystic ovary syndrome

Abstract: Results:Variations in cycle variables with BMI and age showed that IVF cycles were negatively affected by increases in obesity and age. Clinical pregnancy rates were found to be lower in the obese group than in the other groups, particularly in the age group above 35 years; however, this difference could not be proven statistically. Conclusion:The present study evaluated obesity and clinical pregnancy rates in IVF cycles in PCOS patients according to age groups, and particularly in the obese group, the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Our conclusions were consistent with some studies which showed that BMI was negatively associated with ovarian response, but did not remain for implantation rate (McCormick et al, 2008) and live birth rate in PCOS patients (Mulders et al, 2003;Ozgun et al, 2011;Huang et al, 2014). However, our conclusion was contrary to other studies which reported BMI having an adverse effect on the clinical IVF outcomes (Jungheim et al, 2009;Bailey et al, 2014;Cui et al, 2016;Kalem et al, 2016). BMI was also found to have a negative relationship with anti-Müllerian hormone levels (Salmassi et al, 2015;Bernardi et al, 2017;Lefebvre et al, 2017), which is one of the widely recognize markers of ovarian reserve (Fleming et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Our conclusions were consistent with some studies which showed that BMI was negatively associated with ovarian response, but did not remain for implantation rate (McCormick et al, 2008) and live birth rate in PCOS patients (Mulders et al, 2003;Ozgun et al, 2011;Huang et al, 2014). However, our conclusion was contrary to other studies which reported BMI having an adverse effect on the clinical IVF outcomes (Jungheim et al, 2009;Bailey et al, 2014;Cui et al, 2016;Kalem et al, 2016). BMI was also found to have a negative relationship with anti-Müllerian hormone levels (Salmassi et al, 2015;Bernardi et al, 2017;Lefebvre et al, 2017), which is one of the widely recognize markers of ovarian reserve (Fleming et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…The full texts of the remaining 47 studies were reviewed, and 28 were excluded for the reasons detailed in Figure 1 . The remaining 19 studies [ 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] fulfilled the eligibility criteria and were included in this review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there was a variation in the categorizations of overweight and obesity ( Table 1 ), the cut-off used for high BMI was not significantly different between studies. Eleven studies applied the World Health Organization’s (WHO) definitions using the cut-offs of 25 kg/m 2 to define overweight and 30 kg/m 2 for obesity [ 14 , 15 , 16 , 18 , 19 , 21 , 23 , 25 , 26 , 31 , 33 ]. Seven studies utilised 24 kg/m 2 and 28 kg/m 2 as the thresholds for designating overweight and obesity, respectively [ 17 , 22 , 24 , 27 , 28 , 29 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-one studies, involving 283,386 cycles, were included in the per-cycle level analysis. 14,28,30,[33][34][35][36][37]39,[41][42][43]45,48,50,[52][53][54]58,61,64,[66][67][68][69]75,77,78,80,82,83,85,87,89,91,92,[94][95][96][97][98][99][103][104][105][106]112,114,121,126,130 We presented the results for both linear and nonlinear dose-response (P n = 0.08). For linear dose-response relationship, ...…”
Section: Association Between Maternal Prepregnancy Body Weight and Cprmentioning
confidence: 99%